The Role of Social Capital and ICTs in Inter-Organizational Collaboration in a Developing Economy: An Empirical Study of the Finance Industry in Sri Lanka - Nawinna, Dasuni Priyanwada (Curtin University, 2017)
This empirical study develops a theory of how ICT enabled social capital affects interfirm strategic collaboration and performance, through structural modelling approach using survey-data and secondary-data from the Srilankan banking industry. The results suggest multiple dimensions of social-capital positively influence interbank collaboration and performance, and that ICTs, firm-size, age, gender-ratio of directors, ownership, culture, organization structure and previous experience strengthen such effects. The study contributes to a holistic perspective incorporating social, technical and organisational aspects.